The Effect Of Building Shape Modification On Wind Pressure Differences For Cross-Ventilation Of A Low-Rise Building - Cheng, See Yuan (VEETECH Ltd and Allen Press, 2007)
The present study investigates the effect of alteration in the building shape due to some common remodelling practice on the wind pressure differences Δp for cross-ventilation of a semi-detached low-rise building using Computational Fluid Dynamics (CFD). A commercial code ANSYS CFX was employed to solve the flow governing equations. The standard k −ε, renormalisation group (RNG) k −ε and Shear Stress Transport (SST) turbulent models were adopted for comparison and the computed velocity was validated against full-scale measurement data. Results computed with these three turbulent models were able to capture the trend of the measured wind speed at the chosen locations with appreciable discrepancy level. Maximum wind pressure differences Δp for cross-ventilation under the effect of building remodelling was calculated based on the CFD results. At the windward side, highest Δp was provided when expansion is made on the kitchen zone of the back neighbouring house. The house with fencing provided the lowest Δp value. In general, for all types of building remodelling, Δp value for houses on the windward side was higher by 447% (on the average Δp value) compared to the houses on the leeward side.